Study of the Influence of Teachers Teaching Style on Students' Interest in Learning English - Athalia Asa Adventina Br Karo; Sri Ninta Tarigan; Tarida Alvina Simanjuntak (PT FORMOSA CENDEKIA GLOBAL, 2024)
Learning English at the high school level often faces various challenges, especially when it comes to attracting students. Based on initial observations at SMA Swasta Indonesia Membangun Medan for the 2023/2024 school year, it was found that many students in grades x2 and x1 felt less interested in learning English. Factors that may cause this lack of interest include material difficulties, lack of relevance of the material to daily life, multiple intelligences of students, teaching style of teachers and techniques of delegators in teaching. The research methodology used is questionnaires, interviews, and data collection. The types of research used are qualitative data and quantitative data. The findings of this study also aim to determine the influence of teachers' teaching styles on students' interest in learning English. Based on the results of research through interviews with teachers, the factors that affect students' lack of interest in learning English are because students have dominance or multiple intelligence in certain fields. And the results of the questionnaire given summarized that students' interest in learning was in the category of quite good, namely 69.03% out of 50 students. And for the delegator teaching style technique, it is done during the group discussion method because in the discussion students can work collaboratively and become teachers with each other